2014
DOI: 10.1007/s12272-014-0408-3
|View full text |Cite|
|
Sign up to set email alerts
|

A comparative study of DA-9601 and misoprostol for prevention of NSAID-associated gastroduodenal injury in patients undergoing chronic NSAID treatment

Abstract: Misoprostol is reported to prevent non-steroidal anti-inflammatory drug (NSAID)-associated gastroduodenal complications. There is, however, limited information regarding the efficacy of DA-9601 in this context. We performed a comparative study on the relative efficacy of DA-9601 and misoprostol for prevention of NSAID-associated complications. In this multicenter, double-blinded, active-controlled, stratified randomized, parallel group, non-inferiority trial, 520 patients who were to be treated with an NSAID (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 27 publications
(25 reference statements)
0
8
0
1
Order By: Relevance
“…These adverse reactions have emerged as a factor that limits the prescription for patients, such as those suffering from rheumatoid arthritis, who require long-term administration of ACF [9]. DA-9601 is an ethanol extract of Artemisia asiatica and is currently used as a clinical medicine for the treatment of gastritis [10]. Interestingly, it has been reported to have anti-oxidative and antiinflammatory effects on experimentally induced gastrointestinal, hepatic, and pancreatic lesions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…These adverse reactions have emerged as a factor that limits the prescription for patients, such as those suffering from rheumatoid arthritis, who require long-term administration of ACF [9]. DA-9601 is an ethanol extract of Artemisia asiatica and is currently used as a clinical medicine for the treatment of gastritis [10]. Interestingly, it has been reported to have anti-oxidative and antiinflammatory effects on experimentally induced gastrointestinal, hepatic, and pancreatic lesions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The three strains have different effects on TLRs signaling and differently stimulate cytokine production in vitro in immune cells ( 3 , 10 , 11 ). Healthy volunteers received the NSAID indomethacin, which induces mild and reversible damage to the gastrointestinal lining ( 21 24 ). Study participants subsequently consumed one of the three L. plantarum strains or placebo for a week.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a meta-analysis showed that H. pylori eradication was not as effective as proton pump inhibitors for preventing NSAIDs-associated ulcers (Vergara et al, 2005). Even though proton pump inhibitors, H2 blockers and prostaglandin E1 analog display some preventive benefit for gastric ulcer (Cullen et al, 1998;Graham et al, 2002;Hawkey et al, 1998; Lee et al, 2014;Medlock et al, 2013;Raskin et al, 1995 andScheiman et al, 2006), an over 77% adverse effect rate could prevent these drugs from clinical usage (Lee et al, 2014;Raskin et al, 1996). In contrast, studies have demonstrated that herbal medicines can effectively prevent the formation of gastric ulcer with fewer side effects in various animal models, suggesting the potential utilization of herbal medicines for preventing gastric and/or duodenal ulcers.…”
Section: Introductionmentioning
confidence: 99%